Nitrificação de efluentes de reatores anaeróbicos em filtros submersos aerados - Araújo, Raulyson Ferreira de (2009)
Although the good performance in organic matter and suspended solids removal, the anaerobic reactors are unable to remove ammonia nitrogen from sewage, which makes indispensable to include a step of post-treatment for removal of ammonia or nitrate as necessary. This paper presents the performance of a new variant technology, where the nitrification unit, preceded by anaerobic units, is a submerged aerated biological filter, without continuous sludge discharge in their daily operation. The oxygenation system is very simple and inexpensive, consisting of perforated hoses and compressors. The anaerobic reactors are a septic tank with two chambers followed (8.82 m³) and two parallel anaerobic filters (36 m³ each) filled with ceramic bricks and conics plastic parts. Both followed aerated filters were filled with cut corrugated conduit. The study evaluated the behavior of the system with constant domestic sewage flow (10 m³/d) and different aeration conditions, are these: stage 01, when applied air flow of 0.01 m³ air/min in both aerated filter; stage 02, remained in the initial air flow rate in the second aerated filter and increased at the first to 0.05 m³ air/min; at last, at last, in stage 03, the air flow rate of first aerated filter was 0.10 m³ air/min and on the second remained at 0.01 m³ air/min. The filter FA1 received load of 0.41 kg COD/m³.d, 0.37 kg COD/m³.d and 0.26 kg COD/m³.d on phases 01, 02 and 03, respectively. The FA2 received loads of 0.25 kg COD/m³.d, 0.18 kg COD/m³.d and 0.14 kg COD/m³.d on phases 01, 02 and 03, respectively. During stage 01, were found the following results: 98% removals of BODtotal and 92% of CODtotal, with effluent presenting 9 mg/L of BODtotal final average and 53 mg/L of CODtotal average; suspended solids removals of 93%, with a mean concentration of 10 mg/L in the final effluent; 47% reduction of ammonia of FA2 to FAN 's, presenting average of 28 mg NNH3/ L of ammonia in the effluent with; the dissolved oxygen levels always remained around 2.0 mg/L. During stage 02, were found removals of 97% and 95% to BODtotal and suspended solids, respectively, with average final concentrations of 8 and 7 mg/L, respectively; was removed 60% of ammonia, whose final concentration was 16.3 mg NNH3/ L, and nitrate was increased to a final average concentration of 16.55 mg N-NO3/L. Finally, the stage 03 provided 6 mg/L of DBOtotal (98% removal) and 23 mg/L of CODtotal (95% removal) of final effluent concentrations average. At this stage was identified the higher ammonia oxidation (86%), with final effluent showing average concentration of 6.1 mg N-NH3/L, reaching a minimum of 1.70 mg N-NH3/L. In some moments, during stage 03, there was a moderate denitrification process in the last aerated filter. The average turbidity in the effluent showed around 1.5 NTU, proving the good biomass physical stability. Therefore, the results demonstrate the submerged biological filters potential, filled with high void ratio material (98%), and aerated with hoses and compressor adoption, in the carbonaceous and nitrogenous matter oxidation, also generating an effluent with low concentration of solids